Relationship between levels of depression and self-esteem in older adults - Sánchez Domínguez, Juan Pablo; Torres Zapata, Ángel Esteban; Brito Cruz, Teresa del Jesús; Lesciur Mandujano, Dihana Nicholle; Martínez Uc, Yuliana del Carmen (Horizonte Sanitario, 2024)
Objective: The objective of this research was to determine the relationship between levels of depression and self-esteem.Material and Methods: The study approach was quantitative, non-experimental, descriptive and correlational. The sample consisted of 50 older adults between 65 and 90 years of age with a mean age of 71.38, of whom 62% were female (31 women) and 38% male (19 men) residents of an urban neighborhood in Ciudad del Carmen, Campeche, Mexico. For the collection of data on the variable depression, the Geriatric Depression Scale of Yesavage was applied and the Rossemberg Scale was used for self-esteem.Results: For depression, the "no symptoms" level was the most frequency with 56% (n=28) and for self-esteem the "high" level was the most recurrent with 54.0% (n=27). The existence of a moderate negative statistical relationship between the variables studied was determined (r=-0.54).Conclusions: A moderate negative statistical relationship between the variables analyzed was obtained for the population studied; however, based on the review of the literature, this data still disagrees with the findings reported in other studies, which is why it is necessary to continue studying the phenomenon in other populations. Palabras clave: Elderly; Depression; Self-esteem.